1996
DOI: 10.3109/10428199609052428
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m sestamibi scanning in multiple myeloma stem cell transplantation

Abstract: We report the use of technetium-99m sestamibi (MIBI) in a patient with multiple myeloma (MM) undergoing peripheral blood stem cell (PBSC) transplantation. MIBI is a radionuclide agent that is preferentially taken up by malignant tumors. Plain radiographs in a MM patient, taken prior to PBSC transplantation, showed a large right humeral lytic lesion that correlated with increased uptake of MIBI at the same location. MIBI uptake, demonstrating active MM bone disease, was also evident in areas which were normal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The results are comparable to those found with MRI [1]. As this study and others [15] showed that MIBI scanning correlates very well with clinical outcome, it is a good complement of other biological parameters for assessing the bone situation after stem cell transplantation. The reappearance of bone lesions after transplantation with a negative pre-exam is a clear, sometimes a first indication of subsequent relapse.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results are comparable to those found with MRI [1]. As this study and others [15] showed that MIBI scanning correlates very well with clinical outcome, it is a good complement of other biological parameters for assessing the bone situation after stem cell transplantation. The reappearance of bone lesions after transplantation with a negative pre-exam is a clear, sometimes a first indication of subsequent relapse.…”
Section: Discussionsupporting
confidence: 91%
“…There are a few reports in the literature [8,15,18,22] demonstrating its usefulness in the diagnosis of MM and only few MIBI data are available for follow-up after high-dose therapy. The great advantage of this method is the detection of biologically active areas [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sensi-/ 7b94$$1468 11-20-97 08:38:54 canas W: Cancer metabolic demand of tumor cells may promote MIBI high dose chemotherapy and stem cell transplantation in a patient with multiple myeloma. 12 With respect to uptake. MIBI has been shown to be taken up by various malignant tumors, including breast carcinoma, bone lesions, the uptake by malignant bone lesions is greater than that of benign bone lesions.…”
Section: Case Historymentioning
confidence: 99%
“…Malignant tumours maintain higher mitochondrial and plasma membrane potentials than most non‐malignant tissue, by virtue of their increased metabolic requirements, and hence demonstrate increased MIBI concentration (1, 2), which forms the basis for using MIBI in evaluating myeloma. Since 1996, a number of studies (3, 4) have explored the use of MIBI in multiple myeloma, and in comparison with skeletal radiography, MIBI demonstrated higher sensitivity and specificity in the detection of bone marrow involvement.…”
mentioning
confidence: 99%